Are There Any Earnings Managements Of Islamic Banking In Indonesia? (Case Study Of Islamic Banking “X” And “Y”) - Banu Witono; Muhammad Sholahuddin (Universitas Airlangga, 2012)
The objective of this research is to analyze the possibility of Earnings Management in the financial statement of Islamic Banks. The population of research includes Islamic general bank. This research applied purposive sampling with Islamic general banks issuing financial statement within consecutive five years ; 2002 – 2006. The hypothesis of the research is the Earnings Management in the financial statement of Islamic Banking. This research applied the method of Total Accrual Healy (1985) as described in Arfani and Sasongko (2005) to identify Earnings Management. Based on the test performed, the average total accrual for 5 years of research is positive and negative, thus, it can be concluded that there is Earnings Management in the financial statement of Islamic Banking in Indonesia as for case Islamic Bank “X” and “Y”.